Principal’s Supervision in Improving the Quality of Education - Lebu, Hasri; Harapan, Edi; Kesumawati, Nila (Yayasan Sembilan Pemuda Indonesia, 2024)
The purpose of this study is to describe how the principal’s supervision improves the quality of education at SDIT Izzuddin Palembang. The research was conducted at SDIT Izzuddin Palembang. In this study, key informants can provide accurate information about the problems studied by the researcher, namely the principal, teachers, students, and all staff. The method used in this study is the Qualitative Research Method. This study uses data collection techniques, namely observation, documentation, and interviews. This study concludes that the principal carries out regular supervision planning by involving all teachers through meetings and preparing supervision assessment instruments. Lesson plans are essential for evaluating and reflecting on learning. The principal provides input and suggestions, which allows teachers to work together and communicate about materials, methods, and media. The principal visits the class as scheduled and evaluates teachers for improvement. Due to the busy teaching schedule, the principal may have limited time for evaluation and guidance. To overcome this, the principal creates a week or month of supervision, with other team members still being evaluated and guided.